2022
DOI: 10.1002/humu.24380
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype‐driven approaches to enhance variant prioritization and diagnosis of rare disease

Abstract: Rare disease diagnostics and disease gene discovery have been revolutionized by whole‐exome and genome sequencing but identifying the causative variant(s) from the millions in each individual remains challenging. The use of deep phenotyping of patients and reference genotype−phenotype knowledge, alongside variant data such as allele frequency, segregation, and predicted pathogenicity, has proved an effective strategy to tackle this issue. Here we review the numerous tools that have been developed to automate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…However, the use of publicly available tools for assisting variant interpretation and prioritization remains underdeveloped and underutilized. Some studies have recently benchmarked phenotype-driven variant prioritization tools (Jacobsen, Kelly, Cipriani, Research Consortium, et al, 2022;Kelly et al, 2022; and the topic is gradually gaining more relevance. To our We have found that Exomiser performed best in the prioritization of causal variants.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of publicly available tools for assisting variant interpretation and prioritization remains underdeveloped and underutilized. Some studies have recently benchmarked phenotype-driven variant prioritization tools (Jacobsen, Kelly, Cipriani, Research Consortium, et al, 2022;Kelly et al, 2022; and the topic is gradually gaining more relevance. To our We have found that Exomiser performed best in the prioritization of causal variants.…”
Section: Discussionmentioning
confidence: 99%
“…Rare disorders (RD), of which 80% have genetic causes, are estimated to affect approximately 6% of the global population [1,2]. The advent of next-generation sequencing (NGS) has made a profound impact in the human genetics/genomics and medical genetics fields by revolutionizing the way rare disease diagnostics and disease gene discovery are performed [3]. The length of diagnostic odysseys of RD patients can be greatly shortened as genetic variants in all possible disease genes can be assessed simultaneously in an unbiased manner [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Exomiser filtered variants based on criteria such as the type of variants, allele frequencies, qualities of variants from the VCF file, a predefined set of genes, and inheritance patterns [14]. Although the variant filtering process helps improve variant prioritization accuracy, some diagnoses are filtered out because of low quality in the VCF, high allele frequencies, and incomplete penetrance [3]. Despite many attempts to address the problem of false calls affecting the diagnosis of RD patients, there is a fundamental limitation to previous approaches.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations